2011
DOI: 10.1007/s12105-011-0283-x
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Analogue Secretory Carcinoma: The First Submandibular Case Reported Including Findings on Fine Needle Aspiration Cytology

Abstract: We present the first case (male, 35 years old) of a mammary analogue secretory carcinoma occurring in a submandibular gland and document findings on fine needle aspiration cytology. On histology, the tumor displayed characteristic features: circumscribed nodules composed of bland, pink to light red neoplastic cells with low proliferative/mitotic activity arranged in tubular, vaguely cribriform, and microcystic structures containing Periodic acid Schiff-positive, diastase-resistant secretory material. Immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 16 publications
5
92
2
Order By: Relevance
“…In the initial description of MASC, the vast majority (13 of 16) of cases arose in the parotid gland [1], but subsequent publications have shown that while the parotid gland is the most common site of origin (n = 50), MASC may also arise in the oral cavity (n = 27), submandibular gland (n = 8), and accessory parotid gland (n = 1) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In the oral cavity, the lip (n = 9), soft palate (n = 8), and buccal mucosa (n = 5) are the most commonly affected subsites [1,2,4,7,11,12].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial description of MASC, the vast majority (13 of 16) of cases arose in the parotid gland [1], but subsequent publications have shown that while the parotid gland is the most common site of origin (n = 50), MASC may also arise in the oral cavity (n = 27), submandibular gland (n = 8), and accessory parotid gland (n = 1) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In the oral cavity, the lip (n = 9), soft palate (n = 8), and buccal mucosa (n = 5) are the most commonly affected subsites [1,2,4,7,11,12].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In addition, the authors found that these salivary gland tumors shared the immunophenotype and, remarkably, the characteristic ETV6-NTRK3 translocation of secretory breast carcinoma, and they accordingly designated them ''mammary analogue secretory carcinomas'' (MASCs). Since the initial description, MASC has been increasingly recognized, with 70 additional reported cases [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These tumors were termed mammary analogue secretory carcinomas (MASC). Since this initial report, there have been approximately 100 additional cases published [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. These have been previously diagnosed as unusual variants of acinic cell carcinoma, adenoid cystic carcinoma, cystadenocarcinoma, mucoepidermoid carcinoma or adenocarcinoma, NOS.…”
Section: Mammary Analogue Secretory Carcinoma Of the Salivary Glandsmentioning
confidence: 99%
“…Moreover, 8 new cases of MASC have been documented as case reports within last two years [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%